A Comparison of Spectinomycin with Ceftriaxone as Treatment for Uncomplicated Gonorrhea - Shabir Hussain, Amjad Mustafa, Arif Mumtaz, Ghazala Shaheen, Fawad Qaiser, Shafique Ahmad (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare the efficacy of spectinomycin with ceftriaxone as treatment for Uncomplicated Gonorrhea. Design of the Study: It was a cross-sectional survey. Place and Duration of Study: This study was carried at Department of Pharmacology DHQ Teaching Hospital kohat and Khaleefa Gul Nawaz Teaching Hospital Bannu from March 2019 to march 2020. Patients and Methods: For the trial, 200 participants were enrolled. Two groups of 100 patients each were formed by randomly dividing the patients. Injections of spectinomycin (2 gm) and ceftriaxone (500 mg) were administered intramuscularly to Group A and Group B, respectively. After 5 days, all patients underwent reexaminations, and their clinical and laboratory results were noted and reviewed. Results of the Study: When administered spectinomycin, patients in Group A (n = 100) indicated 95% full response, 3% partial response, and 2% no reaction, but when given ceftriaxone, patients in Group B (n = 100) indicated 91% full response, 3% partial response, and 6% no response at all. Furthermore, the aetiology of gonorrhoea infection is not statistically associated with getting older. Conclusion: The cure rates for spectinomycin and ceftriaxone are statistically indistinguishable. However, spectinomycin may only be used in cases of ceftriaxone resistance because it causes pain at the injection site, is less effective for pharyngeal gonorrhoea, and is contraindicated during pregnancy and breast-feeding. Keywords: Neisseria Gonorrhea, Ceftriaxone, Spectinomycin